Manual de patologías de daños y evaluación geo-referenciada de las vías de asfalto correspondiente a los cantones: Atahualpa, Piñas, Portovelo, Zaruma, Balsas, Marcabelí, Chilla, y Las Lajas de la provincia de El Oro - Aguirre Blacio, Carlos Iván (2015)
In the province of El Oro does not have an updated pathologies damage yevaluación manually geo-referenced date of surface condition of the roads of asphalt delos cantons: Atahualpa, Pineapples, Portovelo Zaruma, Balsas, Marcabeli, Chilla, Las Lajas , which generates each year thousands of dollars are invested in the rehabilitation of these. The aim of this work is to develop this work manual in order to: evaluate the surface condition, identify the main mechanisms of damage and develop a database of geo-referenced data pathways under study. For the preparation of the manual bibliographic research and the route of the ways to collect field data, with photographic support the site, a definition of damage, and corrective action was performed. the surface condition of the asphalt roads of the upper area of ​​the main strategic road network in the province of El Oro, was evaluated and obtain information on the current status of the named routes.  The result of this project was: a manual of pathologies of damage which will meet location of the damage, it is expected that this document will be of great help for road engineers when making the right solution. The evaluation georeferenced 77.9 km of roads of this study was determined to be in poor condition 65.30 km, in fair condition 11.4 km and 1.2 km in good condition. Traductor de Google para empresas:Google Translator ToolkitTraductor de sitios webGlobal Market Finder